2008
DOI: 10.2337/db07-0516
|View full text |Cite
|
Sign up to set email alerts
|

Denervation and High-Fat Diet Reduce Insulin Signaling in T-Tubules in Skeletal Muscle of Living Mice

Abstract: OBJECTIVE-Insulin stimulates muscle glucose transport by translocation of GLUT4 to sarcolemma and T-tubules. Despite muscle glucose uptake playing a major role in insulin resistance and type 2 diabetes, the temporal and spatial changes in insulin signaling and GLUT4 translocation during these conditions are not well described.RESEARCH DESIGN AND METHODS-We used time-lapse confocal imaging of green fluorescent protein (GFP) ADP-ribosylation factor nucleotide-binding site opener (ARNO) (evaluation of phosphatidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…The high plasma membrane cholesterol content of 3T3-L1 adipocytes (37) and L6 myotubes cultured in the presence of fatty acids (19) decreases insulin-promoted glucose transport in these cells. Additionally, a recent report indicates that a highfat diet reduces insulin signaling, abolishing phosphatidylinositol 3,4,5-phosphate production and GLUT4 translocation to the T-tubules of live mouse skeletal muscle (35). Moreover, treatment of 3T3-L1 adipocytes with chromium picolinate, a compound that removes membrane cholesterol, activates GLUT4 trafficking and enhances insulin-stimulated glucose transport via a cholesterol-dependent mechanism (10).…”
Section: Discussionmentioning
confidence: 99%
“…The high plasma membrane cholesterol content of 3T3-L1 adipocytes (37) and L6 myotubes cultured in the presence of fatty acids (19) decreases insulin-promoted glucose transport in these cells. Additionally, a recent report indicates that a highfat diet reduces insulin signaling, abolishing phosphatidylinositol 3,4,5-phosphate production and GLUT4 translocation to the T-tubules of live mouse skeletal muscle (35). Moreover, treatment of 3T3-L1 adipocytes with chromium picolinate, a compound that removes membrane cholesterol, activates GLUT4 trafficking and enhances insulin-stimulated glucose transport via a cholesterol-dependent mechanism (10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, morphological analyses have shown that the content of SS mitochondria is increased more than IMF mitochondria following endurance training (13). Advances in confocal imaging techniques have revealed compartmentalized GLUT4 translocation, where GLUT4 vesicle movement of longer distances only took place in the SS region (21), and a high-fat-fed diet reduced GLUT4 translocation in the t-system to a greater extent than in the sarcolemma (22). Furthermore, in carbohydrate metabolism, localization dependency has been found regarding glycogen synthase activity (34), rate of glycogen resyntheses after exercise (25), and role of glycogen in single fiber contractility (29).…”
mentioning
confidence: 99%
“…The notion of differential regulation of GLUT4 recruitment to the sarcolemma and transverse-tubules is further supported by microscopy studies on skeletal muscle from animal models of insulin resistance. In denervated muscle and muscle from fat-fed animals, reductions in GFP-GLUT4 translocation are reported to occur mainly at the transverse-tubule system (Lauritzen et al, 2008b).…”
mentioning
confidence: 99%